LPS-Induced Neuron Cell Apoptosis through TNF-α and Cytochrome c Expression in Dental Pulp - Sampoerno, Galih; Supriyanto, Eddo; Wahjuningrum, Dian Agustin; Larasati, Aghnia Alma; Ardiani, Dinda; Surboyo, Meircurius Dwi Condro; Bhardwaj, Anuj; Ates, Ayver Atav (European Journal of Dentistry, 2023)
Objectives Inflammation of the dental pulp tissue caused by bacteria, creating an immunology response of death of the dental pulp, is called apoptosis. The Porphyromonas gingivalis that cause apoptosis is lipopolysaccharide (LPS) through toll-like receptor (TLR) via two different mechanisms, intracellular and extracellular pathways. This study analyzed the role of LPS exposure of neuron cells, tumor necrosis factor-α (TNF-α), and cytochrome c (cyt-c) expression in the dental pulp to predict the possible mechanism of apoptosis.Materials and Methods The lower tooth of Sprague Dawley rats was opened and exposed to LPS for 48 hours. Then the neuron cell analyzed histopathology using hematoxylin–eosin, whereas the TNF-α and cyt-c expression with indirect immunohistochemistry using a light microscope. The relationship between neuron cells with TNF-α and cyt-c was analyzed using stepwise regression linear analysis.Result The LPS exposure showed a lower number of neuron cells and had a relationship with TNF-α expression but not with cyt-c, while compared with control, both TNF-α and cyt-c expression were higher in neuron cells.Conclusion LPS exposure in dental pulp is possible to stimulate the apoptosis process through extracellular pathways marked by higher TNF-α expression.
Keywords: apoptosis; TNF-α; cytochrome c; dental pulp; neuron cell; immunology